Prognostic Significance of Tumor-Stroma Ratio in Hepatocellular and Gallbladder Carcinomas: A Systematic Review and Meta-Analysis - Ahuja, Sana; Fattahi-Darghlou, Marzieh; Zaheer, Sufian; Jarrahi, Alireza Mosavi; Hashemi Nazari, Seyed Saeed; Al Marzouqi, Amina Mohammed; Rahman, Syed Aziz; Al-Yateem, Nabeel; Darwish Al-Marzouqi, Zalikha Khamis; D'Costa, Maria Pramila (Asian Pacific Journal of Cancer Biology, 2025)
Background: The tumor microenvironment plays a crucial role in cancer progression, with the tumor-stroma ratio (TSR) emerging as a prognostic marker in solid tumors. A high TSR, indicating a greater proportion of tumor cells relative to stromal tissue, has been associated with improved survival. However, its prognostic value in hepatocellular carcinoma (HCC) and gallbladder carcinoma (GBC) remains unclear. This meta-analysis aims to assess the prognostic significance of TSR in these cancers. Materials and methods: A systematic search of PubMed, Scopus, and Web of Science was conducted following PRISMA guidelines. Eligible cohort studies assessing TSR in HCC and GBC were included. Hazard ratios (HRs) for overall survival were pooled using a random-effects model. Heterogeneity was assessed using the I² statistic. The risk of bias was evaluated using the Newcastle-Ottawa Scale. Results: Four retrospective cohort studies with 542 patients were included. A high TSR was significantly associated with improved survival in HCC (HR: 2.566, 95% CI: 1.028–4.104) but showed a weaker, non-significant association in GBC (HR: 1.568, 95% CI: 0.327–2.809). No publication bias was detected (Egger’s test, p=0.552). Conclusion: This meta-analysis highlights TSR as a potential prognostic marker in HCC, where a high TSR is associated with improved survival. In GBC, the prognostic significance of TSR remains uncertain, possibly due to tumor heterogeneity and advanced-stage diagnoses. Given its prognostic value, TSR could be integrated into routine histopathological assessments, particularly in HCC, to enhance risk stratification and guide clinical decision-making.